การลดของคืนจากการส่งมอบฐานรองรับมอเตอร์โดยใช้แนวทางซิกซ์ซิกมา - ชัยพันธ์ พัทธิกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
The objective of this study was solution the quality problem to decrease the return of customer reject of Motor Base which the driver of Hardisk Drive due to Open Circuit and Hi-pot problem that before improvement the process failure was happened 1,157 dppm. The study had used the statistical process control according to Six Sigma approach in 5 steps were 1st step "Define" the problem, 2nd step "Measure" for identify the problem, 3rd step "Analyze" for the root cause of problem, 4th step "Improve" and correct the process and last 5th step "Control" the process, the beginning of the study was define the problem, validate the "Repeatability & Reproducibility" of measurement system then analyze the problem by "Cause & Effect diagram" and then prioritize the root cause by Failure Mode & Effective Analysis, for next step the "Hypothesis test" had been done for test the significant of each factor after that improvement the process by took the "Design of Experiment" and last step verified the result and standardization. After finish the project the defect had reduced to 257 dppm. or reduced 78% comparison base on cost that had been saved 64,732 Baht/Million pcs. or 12,946 Baht/Month/Million pcs.